Maximum Utilization of Google Sites (MUGS) in Teaching English for Academic and Professional Purposes - Data, Norelyn (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
In the new normal education, educators are expected to maximize to use of technology in providing instructional support to the student making them more engaged in the learning process. The study employed a mixed method to determine the positive effects of utilizing a teacher-made google site in teaching English for Academic and Professional Purposes (EAPP) among selected Grade 11 students. Google Sites is a website-building platform tool for the teacher who wants to build an e-learning environment, and a one-stop hub for students to access modules, interactive worksheets, important resources, video lessons, and reminders. The results of descriptive statistics provided evidence of the effectiveness of the intervention in prompting students’ engagement, independent learning, convenience, time management, and submission of outputs. A Paired-Sample T-test was also conducted. It was found that there was a significant gain with a large effect size on the participants' knowledge after the intervention was implemented. An interview questionnaire was also administered to explore the experiences of the participants towards intervention. Through thematic analysis, it was found that students have positive perceptions and good experience in using the teacher-made google as supported by the frequency of the themes derived from their textual responses. These findings imply that the utilization of Google Sites was an effective learning platform during this time of distance learning. It is recommended that schools will adopt and implement this platform with wider scope as it is proven to help students boost their engagement, and independent learning, gives opportunity to take time in understanding the lesson, and easy access to learning materials